NIMH project accept (HPTN 043): Results from in-depth interviews with a longitudinal cohort of community members (2018)
Introduction: NIMH Project Accept (HPTN 043) is a community- randomized trial to test the safety and efficacy of a community-level intervention designed to increase testing and lower HIV incidence in Tanzania, Zimbabwe, South Africa and Thailand. The evaluation design included a longitudinal study with community members to assess attitudinal and behavioral changes in study outcomes including HIV testing norms, HIV-related discussions, and HIV-related stigma. Methods: A cohort of 657 individuals across all sites was selected to participate in a qualitative study that involved 4 interviews during the study period. Baseline and 30-month data were summarized according to each outcome, and a qualitative assessment of changes was made at the community level over time. Results: Members from intervention communities described fewer barriers and greater motivation for testing than those from comparison communities. HIV-related discussions in intervention communities were more grounded in personal testing experiences. A change in HIV-related stigma over time was most pronounced in Tanzania and Zimbabwe. Participants in the intervention communities from these two sites attributed community-level changes in attitudes to project specific activities. Discussio n: The Project Accept intervention was associated with more favorable social norms regarding HIV testing, more personal content in HIV discussions in all study sites, and qualitative changes in HIV-related stigma in two of five sites. © 2014 Maman et al.